Forecasts on The Growth of Brazilian Public Debt 2000-2026 - da Silva Filho, Luis Abel; de Sousa Rocha, Clefney; Moreira de Siqueira, Rogério; de Souza e Silva, Edcleutson (Revista Análise Econômica e Políticas Públicas - RAEPP, 2026)
A country’s public debt is one of the main indicators of deficit control. In Brazil, the exponential growth of public debt in the 2000s, especially from 2016 onwards, has become the subject of extensive academic and institutional debate. In this sense, this study aims to predict the growth of Brazilian public debt using time-series econometrics. Tests indicated that the Autoregressive model. The Integrated Moving Average (ARIMA) (0,2,1), derived from an ETS function, is the most parsimonious for forecasting. The results indicated forecasts with Mean Absolute Percentage. The error (MAPE) was 1.76 in the training dataset and 3.82 in the test dataset. The forecasts made from the training datasets and validated on the test datasets indicate that, for the months of October 2023 to June 2026, Brazil’s net public sector debt trajectory is upward.